Employment Protection and Effort Among German Employees - Riphahn, Regina Therese (Economics letters, 2004)
Using a difference-in-difference approach and cross-sectional data from the German Socioeconomic Panel it is shown that high levels of employment protection increase absenteeism by up to 35 percent or about 3 days per yea
WiSo-Import:2015-03-26:2661
Keywords: absenteeism; public sector; shirking; effort; Employment protection